1997
DOI: 10.1891/0886-6708.12.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Withholding Disclosure of Child Sexual Abuse

Abstract: Researchers have found equivocal results with respect to whether the disclosure of child sexual abuse is helpful or not. The threat of harm as well as the possibility of being humiliated, not believed, or blamed, render the disclosure of child sexual abuse difficult for some victims. Suppressing of traumatic events has been linked to negative health effects. The current study investigated the relationship between the inability to fully disclose the abuse and subsequent traumatic symptomatology. Questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Testa et al (1992), with 231 women recruited from multiple settings, found that disclosers and nondisclosers did not differ with respect to outcomes associated with PTSD, self-esteem, and global functioning. Similarly, Sinclair and Gold (1997) found no differences between disclosers and nondisclosers in severity of trauma-related anxiety and distress with a sample of 204 female college students.…”
Section: Disclosers Versus Nondisclosersmentioning
confidence: 89%
See 1 more Smart Citation
“…Testa et al (1992), with 231 women recruited from multiple settings, found that disclosers and nondisclosers did not differ with respect to outcomes associated with PTSD, self-esteem, and global functioning. Similarly, Sinclair and Gold (1997) found no differences between disclosers and nondisclosers in severity of trauma-related anxiety and distress with a sample of 204 female college students.…”
Section: Disclosers Versus Nondisclosersmentioning
confidence: 89%
“…To date, most studies with adult samples had failed to reveal a link between patterns of CSA disclosure and later psychological functioning among victims (e.g., Finkelhor, 1979;Sinclair & Gold, 1997;Testa et al, 1992). Arata (1998) documented the only clear exception to this pattern of findings, as short-delay disclosers in her college student sample reported fewer symptoms of PTSD-related intrusion and avoidance than a comparison group composed of longdelay disclosers and nondisclosers.…”
Section: Short-delay Disclosers Long-delay Disclosers and Nondisclomentioning
confidence: 99%
“…Most studies specifically examining disclosure of CSA do not find differences in psychological functioning between disclosers and nondisclosers for either children or adults (e.g., Nagel, Putnam, Noll, & Trickett, 1997;Sinclair & Gold, 1997;Testa, Miller, Downs, & Panek, 1992; for a brief review, see Ruggiero et al, 2004). Others have found disclosure to be associated with greater anxiety and difficulty with coping (Elliott & Briere, 1994;Tufts New England Medical Center, 1984).…”
Section: Journal Of Psychological Traumamentioning
confidence: 99%
“…However, delayed discussion of childhood sexual coercion was not significantly related to problematic alcohol and/or drug use in the last year. Discussing experiences of sexual coercion is not necessarily linked to better health/behavior outcomes (Sinclair & Gold, 1997).…”
Section: Introductionmentioning
confidence: 99%